Effects of canary seed on two patients with disseminated granuloma annulare (Dermatology Reports, 2022)
Treatment of disseminated granuloma annulare (GA) can be challenging and there is no gold standard for treatment. We observed two cases of generalized GA that were treated successfully with canary seed milk despite being resistant to other treatments. Canary seed milk has antioxidant (contains vitamin E), anti-diabetic (DPP-4 inhibition), and anti-hypertensive (ACE inhibition) properties. Therefore, dermatologists can consider canary seed milk, also known as alpiste milk, as a sole or supplemental treatment for patients with GA with or without comorbidities such as diabetes and hypertension, who prefer alternative therapy or failed other treatments.